Microvariação na resolução de sujeitos pronominais: português europeu vs. italiano - Madeira, Ana; Fiéis, Alexandra; Teixeira, Joana (Revista da Associação Portuguesa de Linguística, 2021)
The present study investigates the resolution of null and overt subject pronouns in intrasentential contexts, considering the role of animacy in antecedent assignment. Participants were 15 native speakers of EP and 14 of Italian. Each language group was administered two multiple choice tasks (speeded and untimed), which had a 2x2 design, crossing the following variables: animacy of the matrix object (animate vs. inanimate) and type of pronominal embedded subject (overt vs. null). Results indicate that there is microvariation in the resolution of overt pronominal subjects in EP and in Italian: the position of the antecedent is the most relevant factor in EP, whereas, in Italian, the animacy of the antecedent is the preponderant factor. Results also show that there is microvariation in the resolution of null subjects (contra previous claims in the literature): the bias for subject antecedents is weaker in Italian than in EP. Possible reasons for the observed microvariation are discussed in detail.